Reading Cosmology in Establishment of The Noble Settlement in Puyung Village, Central Lombok District - Liza Hani Saroya Wardi; Muhammad Fadjri (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
This paper is intended to explain the reading of cosmological concepts set as the foundation of dwelling in Puyung village, Central Lombok. The questions answered and explained are about who the Puyung really are. What is the universe and how do Puyung people see it? And, how do their knowledges of the universe applied in constructing and organize their environment. In answering those questions, cosmological concepts were reviewed. Historical reference related to their ancestors was used to find out who the Puyung people really were in the larger context of Sasak People. The research method used is the historical method consisting of heuristics, source criticism, interpretation and historiography. Whereas in reading cosmology using hermeneutic and semiotic methods, in addition to using descriptive methods in analyzing in order to find cosmological connectedness with their settlements which make the concept in the formation of their own settlements while collecting data using observation and in-depth interviews with local communities.